Marketing Strategy of KOH Coconut in the Czech Republic - Červená, Pavla (2016)
This thesis inquires marketing strategy of a new beverage brand in the Czech market. By reviewing a relevant literature and reports it helps to understand theoretical concept of creating a marketing plan and its steps. The core of the theoretical part is external and internal situational analysis of the market, customers and a marketing mix. This theory is later applied at the specific case of KOH Coconut brand and its potential launch in the Czech Republic. KOH Coconut is a Taiwanese coconut brand featuring coconut water beverages and other coconut products.